The Reproductive Performance of Local Sheep Following Induced Superovulation With Cattle Hypophisa Extracts - Dwi Mei Hanifah; Suci Andanawari; Haris Tri Wibowo; Rosa Zulfikhar; Dwi Novrina Nawangsari; Sunardi, Sunardi; Dewi Pranatasari; Hendro Sukoco; Annisa Putri Cahyani (Formosa Journal of Applied Sciences, 2023)
The aim of this study was to determine the effect of pituitary extract on estrous characteristics and the percentage of pregnancy in sheep. This study used a sample of 18 individuals. This study used 3 treatments 6 replications. The treatment used was the control treatment by giving 1 ml of PGF2α. Treatment 1 is by administering 1 ml of PGF2α, 1;0.5;0.25 ml of pituitary extract and 1 ml of PGF2α. Treatment 2 is by administering 1 ml of PGF2α, 2;1;0.5 ml of pituitary extract and 1 ml of PGF2α. The results showed that there was a very significant difference in the use of pituitary extract, this could affect the onset of estrus 0.00 (P<0.01), and there was also a significant difference (P<0.05) in the intensity of estrus.